Effective Teaching Methods and Their Analysis in the Learning Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the most effective teaching methods used in modern education and provides a detailed analysis of their application in classroom settings. The study emphasizes the importance of learner-centered approaches such as interactive learning, problem-based learning, and the use of multimedia technologies to enhance student engagement and academic performance. Traditional methods are also compared to innovative techniques to identify the most efficient strategies in various teaching contexts. The role of formative assessment, teacher feedback, and differentiated instruction is also discussed to understand how these components contribute to the effectiveness of teaching. Through qualitative and quantitative analysis, the article aims to guide educators in selecting appropriate methods tailored to the needs of diverse learners, ultimately fostering a more productive and inclusive learning environment.